Cell-Type-Specific Splicing of Piezo2 Regulates Mechanotransduction - Marcin Szczot; Leah A. Pogorzala; Hans Jürgen Solinski; Lynn Young; Philina Yee; Claire E. Le Pichon; Alexander T. Chesler; Mark A. Hoon (Cell Reports, 2017)
Summary: Piezo2 is a mechanically activated ion channel required for touch discrimination, vibration detection, and proprioception. Here, we discovered that Piezo2 is extensively spliced, producing different Piezo2 isoforms with distinct properties. Sensory neurons from both mice and humans express a large repertoire of Piezo2 variants, whereas non-neuronal tissues express predominantly a single isoform. Notably, even within sensory ganglia, we demonstrate the splicing of Piezo2 to be cell type specific. Biophysical characterization revealed substantial differences in ion permeability, sensitivity to calcium modulation, and inactivation kinetics among Piezo2 splice variants. Together, our results describe, at the molecular level, a potential mechanism by which transduction is tuned, permitting the detection of a variety of mechanosensory stimuli. : Szczot et al. find that the mechanoreceptor Piezo2 is extensively alternatively spliced, generating multiple distinct isoforms. Their findings indicate that these splice products have specific tissue and cell type expression patterns and exhibit differences in receptor properties. Keywords: Piezo, touch, sensation, ion-channel, splicing